Protocol for assessing functional impairments in patients with unilateral and bilateral vestibulopathy: a novel approach to evaluate the impact of vestibular loss in daily life setting - Corre, Julie; Grouvel, Gautier; Yadnik, Sai; Cugnot, Jean-François; Ghavami, Sinan; Boutabla, Anissa; Cavuscens, Samuel; Ranieri, Maurizio; van de Berg, Raymond; Armand, Stéphane; Guinand, Nils; Pérez Fornos, Angélica (Frontiers in Neurology, 2025)
BackgroundCurrent vestibular assessments typically focus on isolated reflex pathways, failing to reflect the integrative nature of balance control. Consequently, clinical results often do not align with patient-reported symptoms or functional limitations in daily life.ObjectiveTo develop and present a comprehensive multimodal protocol for assessing functional impairments in patients with unilateral vestibulopathy (UV) and bilateral vestibulopathy (BV) using wearable sensors and ecologically valid daily-life tasks.MethodsWe designed a protocol combining nine inertial measurement units (IMUs), eye-tracking glasses, and plantar pressure insoles to assess participants during 15 standardized tasks reflecting daily activities. Tasks were selected through literature review, validated questionnaires (DHI, VADL), and patient interviews. The protocol is conducted in a semi-naturalistic rehabilitation facility environment to maximize ecological validity while maintaining standardization. We tested feasibility with 60 participants (20 UV, 20 BV, 20 healthy controls).Protocol outcomesThe protocol successfully demonstrates feasibility across all sensor modalities and task categories. In this paper we describe the methodology used for task selection, the results of task performance in people with unilateral and bilateral vestibulopathy and healthy controls, and the sensor methodology (inertial measurement units, eye-tracking glasses, plantar pressure insoles). Analysis of sensor data will be presented in future papers.ConclusionThis protocol provides a patient-centered, ecologically valid framework for quantifying vestibular-related functional impairments beyond traditional laboratory settings. The methodology bridges the gap between clinical vestibular testing and lived patient experiences, enabling objective assessment of real-world mobility challenges for personalized rehabilitation and treatment monitoring.